2014
DOI: 10.4172/2167-1168.1000154
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to conducting multicenter nursing research

Abstract: Introduction: The move towards evidence-based nursing practice requires active participation by nurses at all levels along the continuum of care. Despite this fact, nursing involvement in multicenter research is limited. This not only limits the generalizability of findings, but hinders collaborative and interdisciplinary research networking between hospitals. Reasons for single site nursing research barriers have been explored. Yet, knowledge of the barriers nurses face when they seek to engage in multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…This finding is supported in previous research which explore nurses' utilisation of research both in the Irish setting (Glacken & Chaney 2004, Brenner 2005) and internationally (McCleary & Brown 2003, Breimaier et al 2011, Moreno-Casbas et al 2011, Yoder et al 2014. The competing demands of nurses' professional responsibility to their patients and the demands of a research study can impact on the nurses' ability to commit to the research and ultimately, the sustainability of a study (Boase et al 2012, Lewis et al 2014. The RCT and this qualitative study were conducted at a time of unprecedented fiscal challenges in the Irish health care setting with cost containment and a national recruitment moratorium placing significant pressure on frontline staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is supported in previous research which explore nurses' utilisation of research both in the Irish setting (Glacken & Chaney 2004, Brenner 2005) and internationally (McCleary & Brown 2003, Breimaier et al 2011, Moreno-Casbas et al 2011, Yoder et al 2014. The competing demands of nurses' professional responsibility to their patients and the demands of a research study can impact on the nurses' ability to commit to the research and ultimately, the sustainability of a study (Boase et al 2012, Lewis et al 2014. The RCT and this qualitative study were conducted at a time of unprecedented fiscal challenges in the Irish health care setting with cost containment and a national recruitment moratorium placing significant pressure on frontline staff.…”
Section: Discussionmentioning
confidence: 99%
“…The research team included experienced frontline nursing staff who were engaged in the planning and design of the study, implementing the research protocol, taking consent and assent, assessing the wounds and collecting the data for the RCT. Participating in clinical research in addition to patient care responsibilities can result in competing priorities for nurses in clinical practice (Boase et al 2012, Lewis et al 2014, which can influence the sustainability of a project. The nurses' engagement in the RCT was in addition to their role on the unit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the respondents do not see that nurses are criticized by their peers when they conduct research. However, a study stated that some staff nurses that are employed in facilities where support from colleagues is difficult because of all activities requiring compensation (Lewis et al, 2014). Table 4 Attitude in terms of Barriers to Conducting Research Table 4 presents the attitudes of nurses towards nursing research according to respondents in terms of barriers to conducting research.…”
Section: Attitude Towards Nursing Research In Terms Of Interest and E...mentioning
confidence: 99%
“…Such efforts shall aim to remove any institutional barriers that may interfere with the ability of nurses to be involved in research and to apply such research findings in their daily nursing practice. Indeed, many other more recently published studies had similarly reported that several barriers might have impeded the nurses from acquiring the relevant knowledge and skills for conducting research and utilizing its findings and applying them in daily nursing practice; and examples of these include Bahadori et al, (2016), Chien et al, (2013), Efstratios (2013), , Konwar & Kalita (2018), Lewis et al (2014), Nkrumah et al, (2018), Oluwatosin (2014), Shifaza et al, (2014), Wang et al, (2013), Wu et al, (2019), and Hutchinson & Johnston (2004).…”
Section: Introductionmentioning
confidence: 99%